Genetic Diversity of Porcine Reproductive and Respiratory Syndrome Virus (PRRSV) From 1996 to 2017 in China - Jiang, Yifeng; Li, Guoxin; Yu, Lingxue; Li, Liwei; Zhang, Yujiao; Zhou, Yanjun; Tong, Wu; Liu, Changlong; Gao, Fei; Tong, Guangzhi (Frontiers in Microbiology, 2020)
Porcine reproductive and respiratory syndrome (PRRS) is one of the most devastating diseases of the global swine industry. The causative agent Porcine reproductive and respiratory syndrome virus (PRRSV) was first isolated in China in 1996, and has evolved quickly during the last two decades. To fully understand the virus' diversity and the epidemic situation in the field and to make future predictions possible, 365 PRRSV strains were used to study its evolution and its genome, 353 of which were isolated from mainland China. High diversity was detected among the PRRSV isolates, and the total isolates could be divided into eight subgroups. Among these, strains belonging to the Original HP-PRRSV, NADC30-like, and Intermediate PRRSV subgroups were the major epidemic PRRSV strains circulating in the field, and will play major roles in PRRS epidemics in the future. Deletions, insertions, and recombinations have occurred frequently in the PRRSV genome and deletions were the main driving force of viral evolution before 2006. They may have also contributed to the virus' evolution in a relatively closed environment with low strain diversity.The recombinant strains were divided into three groups: the Inner group, Extensional group, and Propagating group. The routes of recombination in the Propagating group were analyzed and sorted into three types. The evolutionary directions of the isolates in the Extensional and Propagating groups have changed, with increases in recombinant strains and high rates of recombination in recent years, indicating that recombination has played a very important role in the virus' evolution. Isolates that incorporate the advantages of their parental strains will be important in future PRRS control.